The vanishing twin: Diagnosis and implications. (November 2022) - Batsry, Linoy; Yinon, Yoav
Abstract: Vanishing twin syndrome (VTS), defined by first-trimester spontaneous loss of a twin, is a common phenomenon with a reported prevalence of 15–35% of twin pregnancies. The etiology of VTS is obscure. Still, several risk factors have been identified, including an increased number of embryos transferred in pregnancies conceived by in vitro fertilization, an initial increased number of gestational sacs and advanced maternal age. The effect of VTS on obstetric and perinatal outcomes is controversial. Several studies have reported that pregnancies with VTS were associated with increased risk for preterm birth and small for gestational age neonates compared to singleton pregnancies, while others showed no difference in perinatal outcomes. The prevalence of placental vascular and anatomic abnormalities such as small placentas was higher in VTS. These findings lay an essential foundation for understanding how this phenomenon affects obstetric and perinatal outcomes of the surviving pregnancy. Highlights: Vanishing twin syndrome (VTS) is a common phenomenon among multiple pregnancies, occuring in 15–35% of twin pregnancies. Risk factors for VTS include an increased number of embryos transferred and gestational sacs and advanced maternal age. VTS is associated with increased risk of adverse perinatal outcome including preterm birth and fetal growth restriction. No data exist regarding VTS in monochorionic pregnancies and its risk for neurological impairment in the surviving co-twin. Placentas from VTS pregnancies are associated with vascular and anatomic pathologic findings.